Execution Of Court Decisions Against Land Cases - Joe Frank Simon; Franky Samosir (International Asia Of Law and Money Laundering (IAML), 2022)
The execution of land cases that have permanent legal force is the embodiment of the value of justice and legal certainty. All parties must actually respect and and implement both litigants and related third parties. A court decision that has been legally enforceable must still be viewed as a truth, because it must be respected and conscientiously implemented as a moral responsibility and legal responsibility. Normatively regulated on the implementation of court decisions that have permanent powers both in the environment of the General Court and the State Administrative Court. But at the level of implementation encountered obstacles barriers. The execution of the decision of the District Court on land matters with permanent strength gets obstacles from the losing side.The losing party made various attempts to thwart the execution of the court's decision with a permanent ruling,so that in its implementation it used the help of security forces. Similarly, the court on land matters by the Administrative Court is highly dependent on the goodwill of government agencies or agencies.This happens because there is no coercive institution as well as the decision of a civil case.